Augustine’s Theory of Imago Dei in Ming and Qing China - ZHOU, Weichi (Journal of Research for Christianity in China (JRCC), 2025)
Augustine’s theory of the renewal of God’s image in man looks at imago Dei from a soteriological perspective. This article investigates the history of the eastward transmission of Augustine’s theory of Imago Dei, identifying two schools within it: one is the mainstream, upholding the traditional Augustinian “memory—understanding—love” theory of the image of God, and the other is a branch, leaning towards Thomas Aquinas’s “mind—understanding—love” theory of imago Dei. In the Chinese context from the Ming and Qing dynasties on, these schools each, in their own way, suggest admonitions for how to renew the image of God in man.